Minimum wage increases under straightened circumstances - John T. Addison; McKinley L. Blackburn; Chad Cotti (Institute for the Study of Labor (IZA), 2011)
Do apparently large minimum wage increases in an environment of recession produce clearer evidence of disemployment effects than is typically observed in the new minimum wage literature? This paper augments the sparse literature on the most recent increases in the U.S. minimum wage, using three different data sets and the two main estimation strategies for handling geographically-disparate trends. The evidence is generally unsupportive of negative employment effects, still less of a 'recessionary multiplier.' Minimum wage workers seem to be concentrated in sectors of the economy for which the labor demand response to wage mandates is minimal.
urn:nbn:de:101:1-201110263808
Keywords: J2; J3; J4; J8; 330; minimum wages; disemployment; earnings; low-wage sectors; geographically-disparate employment trends; recession; Mindestlohn; Wirkungsanalyse; Beschäftigungseffekt; Konjunktur; Niedriglohn; Schätzung; USA